2006
DOI: 10.1097/01.blo.0000229302.52147.c7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Percutaneous Biopsies of Musculoskeletal Tumors

Abstract: Diagnostic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 15 publications
7
40
0
2
Order By: Relevance
“…1). This finding is commensurate with other reports of lower success with soft-tissue lesions [14,15,20].…”
Section: Discussionsupporting
confidence: 82%
“…1). This finding is commensurate with other reports of lower success with soft-tissue lesions [14,15,20].…”
Section: Discussionsupporting
confidence: 82%
“…A previous study analyzed the combination of NCB and FNAC and found 63% were useful to guide treatment and 26.5% required open biopsy [22]. The clinical usefulness of FNAC for evaluation and management of soft tissue masses is based on whether the technique reliably supplies adequate information for initial triage and selection of appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear, however, that nondiagnostic (ND) needle biopsies are a challenge to clinicians, pathologists, and patients as they potentially delay diagnosis and treatment and increase patient anxiety [20]. Published series have documented that overall ND rates for image-guided needle biopsies range between 5% and 29% [1,8,15,17]. Specific diagnoses rarely are reported to have an effect on the ND rates [14,15], although sclerotic or necrotic lesions are more difficult to diagnose [3,7,8,14].…”
Section: Introductionmentioning
confidence: 99%
“…The image-guided needle biopsy is an established method used to diagnose musculoskeletal tumors [9,17]. There has been a shift away from open incisional biopsies at major cancer centers as interventional radiologists and musculoskeletal pathologists gain skills in procuring and processing core biopsies and fine-needle aspirates [2,4,5,21].…”
Section: Introductionmentioning
confidence: 99%